The Unstable Nature of Dominant-Subordinate Relation: Postcolonial Study Towards Thomas King’s 'The Colour of Walls' - Sardari, Alireza (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Aboriginal/Indigenous peoples, cultures and works of literature (in the broadest sense) play a crucial role in the continuous growth of world literary and cultural studies. Indigenous writers advocate indigenous rights and address their concerns in works of fiction and non-fiction. Focusing on the correlation between the dominant (center) and the subordinate (margin) in Thomas King’s The Colour of Walls (2013), the present paper aims to specifically investigate the dominant-subordinate interplay in the colonial discourse. So as to elucidate this labyrinthine network of relationships, Homi Bhabha’s critical concept of hybridity is employed throughout the analysis process. The results indicate the unstable nature of dominant-subordinate dichotomy in the story, where power-based relationships are subject to constant change. Accordingly, this process of cultural struggle provides a site for the subordinate to change their marginal position and to resist the dominant’s influence; ultimately, this process assists the subordinate to reclaim their own independent identity.